Relato de experiência: narrativas autobiográficas de crianças e sua relação com o saber da dança no ensino remoto emergencial - Amaral, Pedro Gabriel Viana do (2021)
The present paper aimed to describe and reflect on an experience of teaching dance classes in the context of Emergency Remote Learning, due to the Covid-19 Pandemic, and to understand how the children related to this teaching object, through autobiographical written and iconographic narratives. Therefore, having as a source the narratives constructed by the children from the evaluation of this Thematic Unit, it was possible to comprehend that they related to the dance knowledge by discovering and enjoying new ways of locomotion, pulsating, memorizing and symbolizing the practices, constituting a relational knowledge.